Entry of painters in the Amsterdam market of the golden age - Federico Etro; Elena Stepanova (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
We analyze the evolution of the price of paintings in the XVII century Amsterdam art market to test a hypothesis of endogenous entry: higher profitability should attract more entry of painters, which in turn should lead to artistic innovations and more intense competition. We build a price index for the representative painting inventoried in Dutch houses through hedonic regressions controlling for characteristics of the paintings (size, genre, placement in the house), the owners (job, religion, value of the collection, size of the house) and the painters. After a peak at the beginning of the century, the real price of paintings decreases until the end of the century: we provide anecdotal evidence for which high initial prices attracted entry of innovators, and econometric evidence on the causal relation between price movements and entry of painters. The time series analysis supports the idea for which increasing prices attracted entry of innovative painters.
Keywords: Z11; N0; D4; 330; Art market; Endogenous entry; Dutch Golden Age; Hedonic prices; VAR analysis